Dual hybrid energy storage device with a battery–electrochemical capacitor hybrid cathode and a battery-type anode - Vijayan, Bincy Lathakumary; Yasin, A.; Izan Izwan, Misnon; Anilkumar, Gopinathan M.; Hamed, F.; Yang, Chun-Chen; Jose, Rajan (American Chemical Society, 2021)
The design of appropriate material architectures and a judicious combination of storage modes are expected to deliver electrical energy storage devices of larger specific energy (ES) and specific power (PS). Herein, a battery-electrochemical capacitor hybrid material as a cathode [i.e., porous carbon filled with three-dimensional MnCo2O4 nanoflowers (3DMCNF), 3DMCNF-AC] and a corresponding battery component (3DMCNF) as an anode are used in a dual hybrid device using a 1 M LiPF6 electrolyte. The cathodic and the anodic properties of the electrodes are separately studied in the half-cell configuration with respect to the Li/Li+ electrode. The 3DMCNF-AC hybrid cathode showed larger specific capacitance (∼165 F·g-1) in the potential range (∼2 to 4.5 V vs Li/Li+) than that of a pure porous carbon cathode (∼115 F·g-1, ∼2 to 4 V vs Li/Li+) at 100 mA·g-1 cycling. The half-cell 3DMCNF anode showed a discharge capacity of ∼1020 mA·h·g-1 in the potential range of ∼0.01-3.0 V versus Li/Li+ at a similar cycling condition to that of the cathode. The dual hybrid full device delivered ∼3.5 V with an ES of up to ∼153 W·h·kg-1 and a PS of up to ∼3500 W·kg-1.